Lean Manufacturing Approach to Improve Speaker Manufacturing Process - Lestari, Nastiti Puji; Karningsih, Putu Dana (IPTEK Journal of Proceedings Series, 2020)
PT Y is a subsidiary of Y Group which specializes in producing speakers for local and international markets. At present PT Y's orders have not met the expected performance targets. Fulfillment of production orders reached 97.55% of the target of 100%. This is one of the concerns of Y Group that PT Y need to improve themselves because it can result in companies becoming less competitive than competitors. Based on preliminary observations, there was indications of waste, namely defects, downtime, and process delays. The lean tool used for further waste analysis is Lean Assessment Matrix (LAM). The results of the research show that the waste which gives the most significant influences are transportation, waiting and inventory. The root causes of problems between work stations are not ergonomic, do not have preventative maintenance schedules, there are no standards for handling defective products, the layout of the room is not in the direction of material, the carrying capacity of hand trucks is small, and the Outgoing Quantity Check (OQC) processes are not included in the company’s time standards. The proposed improvement recommendations include conducting training to improve product repair skills, relayout of production plant, and making a preventative machine maintenance schedule.